The role of teacher-student developmental relationships in linking communicative language teaching and communicative competence - Zhou, Danqiangyu; Li, Qing (Frontiers in Psychology, 2025)
Interaction between educators and students plays a crucial role in shaping educational processes and outcomes. This study investigates the relationship between Communicative Language Teaching (CLT), Form-Focused Instruction (FFI), and communicative competence among Chinese English language learners, with a particular focus on the mediating role of teacher–student developmental relationships. Data were collected from 891 Chinese college students learning English as a foreign language. Results showed that CLT was positively associated with teacher–student developmental relationships, while FFI was negatively associated with them. Teacher–student developmental relationships, in turn, were strongly associated with students’ communicative competence. Importantly, CLT and FFI did not show significant direct effects on communicative competence, indicating that their influence operates indirectly through relational dynamics. These findings highlight the central role of teacher–student relationships in explaining how teaching approaches are linked with communicative competence. Given the cross-sectional design and the moderate reliability of some scales, results should be interpreted as exploratory. Future research with updated measurement tools, objective assessments, and longitudinal designs is needed to validate these associations.